EU Green Transition in Times of Geopolitical Pressures: Accelerating or Slowing the Pace Towards Climate Neutrality? - Pérez de las Heras, Beatriz (European Journal of Sustainable Development, 2024)
The current climate emergency and the war in Ukraine have placed climate action and energy security at the top of the EU’s agenda. The ‘Fit for 55’ legal package and REPowerEU Plan set out short- and medium-term measures to end EU dependence on Russian fossil fuels and address climate change. The new targets and policy instruments have the potential to accelerate decarbonization of the continent. However, from the perspective of the environment and social equity, serious concerns remain as to the sustainability of the transformation. For example, difficulties in achieving immediate independence from Russian fuels has led some EU countries to increase their use of coal. The accelerated roll-out of renewable energies has increased the demand for materials and land, sparking territorial conflicts and impacting biodiversity. Support from the Social Climate Fund will not meet all the demands of the most vulnerable sections of society for assistance with the costs derived from the energy transitions, such as cleaner heating systems and transport. This paper offers an overview of the EU’s new measures to step up the energy transformation and assesses them through the lens of environmental sustainability and fair transition. Keywords: renewable energy, energy autonomy, REPowerEU, fair transition